P072 Irf1 is critical for the inflammatory gene expression in fibroblast-like synoviocytes. (21st February 2018) - Bonelli, M; Hayer, S; Dalwigk, K; Niederreiter, B; Pap, T; Smolen, J; Kiener, H; Karonitsch, T
Abstract : Introduction: Fibroblast-like synoviocytes (FLS) are increasingly recognised as major pathogenic cells in synovial inflammation of patients with Rheumatoid Arthritis (RA). In response to pro-inflammatory stimuli, such as TNF, FLS produce vast amounts of cytokines and chemokines that help to recruit and activate immune cells and drive the local inflammatory process. The pathways and transcription factors that determine the inflammatory response in FLS are, however, largely unexplored. Objectives: To investigated the potential contribution of the transcription-factor IRF1 to the inflammatory gene expression in FLS. Methods: Expression of IRF1 in synovial tissue samples (12 RA and 8 osteoarthritis (OA) patients) was assessed by immunohistochemistry (IHC). Moreover, FLS were isolated according to established protocols and cultured using 2-D or 3-D culture techniques. IRF1expression in response to TNF was determined by western blots, qPCR, immunofluorescence microscopy or IHC. FLS were also stimulated with TNF in the presence or absence of IRF1 siRNA pools. Expression of pro-inflammatory cytokines and chemokines was measured by qPCR. Results: IRF1 expression was significantly increased in rheumatoid synovial tissues as compared to patients with OA on protein level. RA-FLS stimulation with TNF ex vivo caused rapid upregulation of IRF1 and proved the involvement of TNF in the regulation of IRF1. Immunofluorescence analysis further revealed that IRF1 was mainly localised in the nucleus of TNF-stimulated FLS. Moreover, also chronic TNF exposure of FLS grown in a 3-D synovial tissue culture system promoted the expression of IRF1. siRNA-mediated knockdown of IRF1 in FLS significantly reduced the TNF-induced expression of pro-inflammatory cytokines and chemokines, such as IL6, CCL7, CXCL11 and TNFSF13B, which confirmed the role of IRF1 as a critical regulator of proinflammatory genes in RA FLS. Conclusions: Our data reveal that IRF1 is crucial for the inflammatory response of FLS and support the idea that IRF1 might be an exciting therapeutic target in patients with RA. Disclosure of interest: None declared